ChatGPT's Role in Helping Leaders Address Communication Challenges in the Digital Age - Vivin Tri Astuti; Iswahyu Pranawukir; Filda Angellia; Veronika Yuni Trisnowati; Maria Jashinta Elisabet Hamboer (Jurnal Minfo Polgan, 2023)
In today's digital age, communication is a very important aspect of leading an organisation. Organisational leaders must be able to overcome communication challenges arising from technological changes and paradigm shifts in the way people interact. The purpose of this research will conduct a comprehensive literature review to explore existing research and literature on the role of ChatGPT in helping leaders overcome communication challenges in the digital era. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results state that ChatGPT plays an important role in helping leaders face communication challenges in the digital era. In its role as a virtual assistant, the model can help leaders craft effective messages, respond quickly, translate languages, and strengthen digital presence. ChatGPT can help leaders cope with the speed and volume of information, manage misunderstandings, analyse sentiment, deal with communication crises, build relationships with audiences, provide insights and up-to-date information, and manage internal and external communications.